2012
DOI: 10.1208/s12249-012-9778-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug Release Profile from Patches Based on Styrene–Isoprene–Styrene Block Copolymer: The Effect of Block Structure and Plasticizer

Abstract: Abstract. We prepared pressure-sensitive adhesive (PSA) patches based on styrene-isoprene-styrene (SIS) thermoplastic elastomer using hot-melt coating method. The liquid paraffine is added in the PSA matrices as a plasticizer to moderate the PSA properties. Three drugs, methyl salicylate, capsaicin, and diphenhydramine hydrochloride are selected as model drugs. The Fourier transform infrared spectroscopy, differential scanning calorimetry test, and wide-angle X-ray diffraction test indicate a good compatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…[11] However, their non-polarity feature greatly limits their applications in different fields due to their poor adhesion with polar materials or weak compatibility with hydrophilic components. [12][13][14] Although aromatic modification or addition of polar tackifiers, such as rosin and its derivatives, can be utilized to increase the polarity of the SIS-based HMPSAs, their partial compatibility with the styrene end-block may compromise its integrity, reducing its strength and softening point. [3,11,15] Because SIS-based HMPSAs are mainly formulated with the SIS copolymers, tackifier resin, and antioxidant, [16][17][18][19][20] their polarity can be improved by various chemical modifications of the SIS copolymers, including graft, sulfonation, plasma, and epoxidation treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] However, their non-polarity feature greatly limits their applications in different fields due to their poor adhesion with polar materials or weak compatibility with hydrophilic components. [12][13][14] Although aromatic modification or addition of polar tackifiers, such as rosin and its derivatives, can be utilized to increase the polarity of the SIS-based HMPSAs, their partial compatibility with the styrene end-block may compromise its integrity, reducing its strength and softening point. [3,11,15] Because SIS-based HMPSAs are mainly formulated with the SIS copolymers, tackifier resin, and antioxidant, [16][17][18][19][20] their polarity can be improved by various chemical modifications of the SIS copolymers, including graft, sulfonation, plasma, and epoxidation treatments.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have been used to introduce polar functional groups in the styrene or diene blocks of the styrenic block copolymers. [12,[21][22][23][24][25][26][27] Among these methods, the epoxidation procedures are utilized to incorporate epoxide groups into the diene blocks of the copolymers, in which some oxidants, such as metal catalyzed/hydrogen peroxide, dimethyldioxirane, meta-chloroperbenzoic acid, and in situ per-formic acid, have been adopted. [22,[28][29][30] To synthesize templates for nanostructured thermosets, metal catalyzed/hydrogen peroxide, dimethyldioxirane, and meta-chloroperbenzoic acid have been utilized to epoxidize SIS or SBS copolymers with high epoxidation degrees (>60 mol%).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that SIS-based HMPSA is compatible with lipophilic drugs and can release drugs continuously (8). Recently, it was found that drug release from HMPSA is related to its cohesion, the structure of the polymer, and the plasticizer content in the formulation (9,10). These studies pioneered the use of SIS-based HMPSA in the field of transdermal drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…To increase their compatibility with polar materials, various strategies are used to introduce polar functional groups in both the styrene and diene blocks, including graft, sulfonation, plasma, and epoxidation treatments . Among these methods, the epoxidation procedures are utilized to incorporate epoxide groups into the diene blocks of the copolymers, in which some oxidants, such as metal catalyzed/hydrogen peroxide, dimethyldioxirane, meta‐chloroperbenzoic acid and in situ peracetic acid, have been adopted .…”
Section: Introductionmentioning
confidence: 99%